A SYSTEMIC FUNCTIONAL LINGUISTIC ANALYSIS OF PRE-SERVICE TEACHERS' ABILITY AND DIFFICULTIES IN WRITING DISCUSSION TEXTS - Budiarti, Dian (2015)
This article presents the findings of a Systemic Functional Linguistic analysis of Discussion texts developed by six pre-service teachers from a state university in Bandung, Indonesia, particularly to reveal their ability and difficulties in writing such texts. This study employed a descriptive-qualitative case study design. The data were obtained by collecting the pre-service teachers' Discussion texts and conducting interviews with the pre-service teachers to help facilitate deeper interpretation. This study found out that most of the pre-service teachers were able to implement appropriate linguistic features of a Discussion text and apply various types of Theme and Thematic progression to produce cohesive and coherent texts. However, most of them appeared to have unstable knowledge about the schematic structure of Discussion text and they needed some improvements particularly in terms of generating ideas, text organization, grammatical structure, and creating appropriate citation. Thus, the pre-service teachers needed explicit guidance to develop a good Discussion text to enrich their content knowledge in order to fulfil the teacher professional competence as required by the Ministry of Education in Indonesia. Keywords: Systemic Functional Linguistics, Pre-Service Teachers, Discussion Texts ABSTRAK Artikel ini mempresentasikan temuan dari analisis Linguistik Sistemik Fungsional pada teks Diskusi yang dikembangkan oleh enam calon guru dari sebuah universitas negeri di Bandung, Indonesia, terutama untuk mengetahui kemampuan serta kesulitan-kesulitan yang dialami mereka dalam menulis teks tersebut. Penelitian ini menggunakan studi kasus deskriptif-kualitatif. Data diperoleh dengan mengumpulkan teks Diskusi para calon guru dan melaksanakan interviu dengan mereka guna membantu menghasilkan interpretasi yang lebih dalam. Penelitian ini menemukan bahwa mayoritas dari mereka sudah mampu mengimplementasikan fitur linguistik teks Diskusi dengan tepat dan menerapkan berbagai tipe Tema dan progresi Tema guna menghasilkan teks yang kohesif dan koheren. Namun di sisi lain, mayoritas dari mereka nampak masih memiliki pengetahuan yang tidak stabil mengenai struktur skematik teks Diskusi dan mereka juga membutuhkan peningkatan terutama dalam hal pengembangan ide, pengorganisasian teks, struktur bahasa, dan pengutipan. Oleh karenanya, para calon guru membutuhkan pengarahan secara ekplisit untuk mengembangkan sebuah teks Diskusi yang baik guna memperkaya pengetahuan isi mereka demi memenuhi kompetensi profesional guru sebagaimana telah diatur oleh Menteri Pendidikan di Indonesia. Kata Kunci: Linguistik Sistemik Fungsional, Calon Guru, Teks Diskusi